1999
DOI: 10.1038/sj.bjp.0702512
|View full text |Cite
|
Sign up to set email alerts
|

Activation of nitric oxide synthase by β2‐adrenoceptors in human umbilical vein endothelium in vitro

Abstract: 1 Some animal studies suggest that b-adrenoceptor-mediated vasorelaxation is in part mediated through nitric oxide (NO) release. Furthermore, in humans, we have recently shown that forearm blood¯ow is increased by infusion of b 2 -adrenergic agonists into the brachial artery, and the nitric oxide synthase (NOS) inhibitor N G -monomethyl-L-arginine (L-NMMA) inhibits this response. 2 The purpose of the present study was to determine whether stimulation of human umbilical vein endothelial b-adrenoceptors causes v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
133
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(141 citation statements)
references
References 43 publications
8
133
0
Order By: Relevance
“…An alternative explanation for the findings must therefore be sought. Alterations in Ca 2+ signalling have been described in diabetes [36,37], although this is unlikely to affect βAR-mediated NOS3 activation, as this activation has been shown to occur without detectable changes in intracellular Ca 2+ either in human vascular endothelial cells [38] or in platelets [6]. It has been reported that sheer stress can activate NOS3 in a Ca 2+ -independent manner [39].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation for the findings must therefore be sought. Alterations in Ca 2+ signalling have been described in diabetes [36,37], although this is unlikely to affect βAR-mediated NOS3 activation, as this activation has been shown to occur without detectable changes in intracellular Ca 2+ either in human vascular endothelial cells [38] or in platelets [6]. It has been reported that sheer stress can activate NOS3 in a Ca 2+ -independent manner [39].…”
Section: Discussionmentioning
confidence: 99%
“…In umbilical vein endothelial cells, it has been demonstrated that ␤ 2 AR stimulates eNOS activation. 4 However, most studies in other preparations have failed to demonstrate an active release of NO in response to ␤AR agonists. 21 Therefore, we first confirmed that ISO in normotensive rat aorta endothelial cells can induce eNOS activation and also demonstrated that AD␤ 2 AR treatment can enhance this response.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Indeed, both ␤ 1 ARs and ␤ 2 ARs are expressed on endothelial cells, 3 and stimulation of endothelial ␤ 2 ARs causes endothelial nitric oxide synthase (eNOS) activation and NO release in human umbilical vein endothelium. 4 In hypertension, ␤AR control of vasorelaxation is impaired, and this impairment seems to be involved in high blood pressure. 5 There are two alternative hypotheses to explain this alteration.…”
mentioning
confidence: 99%
“…b-adrenoceptors change endothelial function eNOS in isolated endothelial cells (Ferro et al, 1999, Isenovic et al, 2002 and iNOS in cultured vascular smooth cells (Koide et al, 1993) following b-adrenoceptor stimulation. In addition, we found a significant increase in protein concentrations for both eNOS and nNOS in aortas from ISO-treated rats.…”
Section: Apc Davel Et Almentioning
confidence: 99%
“…In addition, activation of b-adrenoceptors on the endothelium produces vasodilatation (Gray & Marshall, 1992;Brawley et al, 2000) that is mediated by the synthesis of nitric oxide (NO) (Ferro et al, 1999). It is possible that chronic b-adrenergic stimulation could induce adaptive alterations of vascular b-adrenoceptor signalling pathways resulting in endothelial dysfunction, impaired peripheral vasodilatation and/or inappropriate vasoconstriction.…”
Section: Introductionmentioning
confidence: 99%